Unfreezing Disney’s Frozen through playful and intentional co-authoring/co-playing - Hewes, Jane; Whitty, Pam; Aamot, Brittany; Schaly, Erica; Sibbald, Jennifer; Ursuliak, Kayla (Canadian Journal of Education/Revue canadienne de l’éducation, 2016)
Often children’s opportunities to play are constrained by particular interpretations of play that instrumentalize its value in the service of adult-defined, future-oriented goals for children. As an alternative, we draw upon specific theoretical insights of play and playfulness, to closely examine the power of the present and past in childhood and adulthood, through ongoing play episodes created and re-created by co-playing, co-authoring adults and children. This particular playing collective takes up common popular cultural scripts embedded in the film Frozen, and through intertextual and multimodal adventuring, indoors and out, reveal emergent and playful uncertainties and potentialities that can occur when children and adults are committed to play as “a thing by itself” (Huizinga, 1950, p. 45).